Oxidation-reduction potential (ORP) as a tool for process monitoring of H2O2/LPMO assisted enzymatic hydrolysis of cellulose. (November 2019) - Kadić, Adnan; Chylenski, Piotr; Hansen, Mads Anders Tengstedt; Bengtsson, Oskar; Eijsink, Vincent G.H.; Lidén, Gunnar
Graphical abstract: Highlights: Oxidation-reduction potential (ORP) can be used for monitoring of LPMO activity. Oxidation-reduction potential (ORP) can be used to control H2 O2 feeding. The LPMO reaction is easier to control in anaerobic conditions. Abstract: Oxidation-reduction potential (ORP) is an environmental factor of importance in several biological conversion processes. Lytic polysaccharide monooxygenases (LPMOs) catalyze oxidative disruption of the cellulose chain in the presence of oxygen or hydrogen peroxide and increase enzymatic hydrolysis yields. However, the enzymes are also sensitive to oxidative damage and the level of oxidative agent needs to be controlled to avoid inactivation of the LPMOs. In the current study, enzymatic hydrolysis of sulfite-pretreated softwood (12% DM loading) was carried out in lab scale reactors with gradual addition of hydrogen peroxide using an LPMO-containing commercial enzyme cocktail. The ORP was measured during enzymatic hydrolysis together with released glucose and the level of C4-oxidized dimer as a marker for LPMO activity. Arrests in LPMO activity coincided with a markedly changed ORP signal and this was utilized in subsequent experiments in which the feed rate of hydrogen peroxide was controlled by keeping the ORP at predetermined set-points of -40 mV, -80 mV and -120 mV. Under anaerobic conditions, the highest hydrolysis yield (78% after 72 h) was found for the ORP set-point of -80 mV. The results show that ORP can serve as an indicator of LPMO activity and may help optimizing overall process efficiency.